Karakteristik Fisik dan Sensori Nuget Tahu dengan Penambahan Keju Cedar dan Keju Cedar Pupa Eri - S. Ramadhani; E. Taufik; A. Apriantini; Taufik, Epi; Apriantini, Astari (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
The increasing demand for nutritious food has driven innovations such as tofu nuggets, yet their blandtaste and limited sensory appeal remain a challenge. The addition of cheddar cheese can enhance flavor,while eri pupae provide high protein and sustainability benefit, making eri pupae cheese a promisingingredients to improve both sensory quality and nutritional value. This study evaluate the physicaland sensory characteristics of tofu nuggets with the addition of cheddar and eri pupae cheese. Fiveformulations were tested, including control and combinations with 5% and 10% cheddar or eri pupaecheese. Physical parameters such as pH and water activity (aw), and sensory attributes, including color,odor, taste, texture, and overall preference, were assessed using hedonic and hedonic quality tests with 35 semi-trained panelists. Results showed that adding cheddar and eri pupae cheese significantly increased pH (P<0.05), while aw remained unchanged. Nuggets with 10% eri pupae cheese (P5) obtained the highest scores for color, texture, and overall liking, due to natural pigments and emulsifying properties, while taste remain unchanged. These findings suggest that combining cheddar and eri pupae cheese can enhance the sensory quality of tofu nuggets, supporting the use of alternative proteins in sustainable food innovation.